1985
DOI: 10.1111/j.1365-3180.1985.tb00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Problems in control of Rottboellia exaltata L.f. in maize in Bukidnon Province, Mindanao, Philippines

Abstract: Summary Various methods were tested to control the annual grass Rottboellia exaltata L.f. in maize (Zea mays L.) under small‐farm conditions in Bukidnon Province, Mindanao, Philippines during 1977 and 1978. No single method was satisfactory. Despite adequate early season control, late‐germinating Rottboellia tillered profusely. By harvest, plots had heavy infestations and were carpeted with seed. At harvest, untreated controls averaged 8·6 t Rottboellia dry matter ha−1 and only half the maize yield of handweed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…These approaches offered the highest level of weed control efficacy compared with the other practices. However, in agreement with Fisher et al (1985), cost of treatments compared with herbicides limits their application to small-scale operations only.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…These approaches offered the highest level of weed control efficacy compared with the other practices. However, in agreement with Fisher et al (1985), cost of treatments compared with herbicides limits their application to small-scale operations only.…”
Section: Resultsmentioning
confidence: 80%
“…Further, no harvestable yields of mungbean were obtainable as the crop came into maturity at a time when it was difficult to get into the maize field. Fisher et al (1985) found that mungbean as a companion crop was promising as a practical control measure if conditions allowed vigorous crop growth. It is suggested that mungbean used as a living mulch is only suited to the situation where small-scale farmers grow maize at wide spacings and low plant densities.…”
Section: Resultsmentioning
confidence: 99%
“…Com relação ao manejo de capim-camalote, a rotação de culturas permite reduzir a associação entre o capim-camalote e algumas culturas possibilitando o manejo com controles alternativos, enquanto que a monocultura facilita que o capim-camalote seja dominante como planta daninha (FISHER et al, 1985). Freitas et al (2004), obtiveram controle de plantas adultas de capim-camalote apenas com sulfoniluréias, constatando que a capina manual proporciona alto índice de reinfestação da área, sendo que essa espécie, pode provocar reduções de até 80 % de produtividade das culturas (HOLM et al, 1977).…”
Section: Introductionunclassified
“…In the tropics, weed life cycles may be extremely short. Echinochloa colona, Setaria verticillata and D. aegyptium approach flowering in 30-45 days whilst Rottboellia cochinchinensis produced mature seeds within 50 days of establishment (Fisher et al 1985). Similar short duration life cycles may also be observed in weeds of temperate latitudes (e.g.…”
Section: Growth Stages Of Fimbristylis Miliaceamentioning
confidence: 55%